2010
DOI: 10.1071/he10130
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, barriers, social support, and environmental influences related to diabetes risk behaviours among women with a history of gestational diabetes

Abstract: Women's ability to follow a healthy lifestyle is embedded in their psychological wellbeing and the social and cultural context of their lives. The study highlights the need for a holistic approach that ensures personal support and access to services as well as lifestyle specific programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 22 publications
2
107
0
Order By: Relevance
“…This study, in agreement with others [11,14,10,18], found that the overseas-bornwomen experienced additional barriers; lack of partner, family and social support resulting in isolation and stress, and diverse cultural preferences and expectations.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This study, in agreement with others [11,14,10,18], found that the overseas-bornwomen experienced additional barriers; lack of partner, family and social support resulting in isolation and stress, and diverse cultural preferences and expectations.…”
Section: Discussionsupporting
confidence: 80%
“…These studies reported barriers such as lack of assistance with childcare, mental distress, low partner and social support, resulting in poor compliance with the healthy lifestyle following childbirth [10,11,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of dietary modifications to support weight loss has been used extensively to treat obesity world-wide, and in high risk populations such as women previously diagnosed with GDM (15, 27, 87, 95). As previously described, women diagnosed with GDM adhere to suggested dietary modification during their pregnancy generally well, although it has also been suggested that this is due to concern for their baby and the wish for an uncomplicated pregnancy, rather than long term life changes (23,85). Overall, participants received the nutrition coaching sessions positively, with most attending at three out of four sessions.…”
Section: Summary Of Key Findingsmentioning
confidence: 83%
“…Moreover, the women in this study were predominately caucasian, and in their mid-thirties, and thus these results may not apply to women of other ages or racial/ethnic groups. Younger women may have lower perceptions of risk and less motivation to alter behaviour (54,84), and women of other races/ethnicities may have different perceptions and understanding of lifestyle changes required to decrease their risk of developing T2DM (85).…”
Section: Limitationsmentioning
confidence: 99%